PKM Pendampingan Pengembangan Media Pembelajaran Berbasis Lingkungan pada Materi Bahasa Arab di Madrasah Tsanawiyah Nurul Jadid Paiton Probolinggo - Sulton Firdaus; Nafahatus Sahariyyah; Elok Azimatuz Zahroh; Dwi Riskiyanti; Zahrotul Aini; Anwar Nuris (Universitas Nurul Jadid, 2021)
Learning Arabic is one of the materials in many madrasas that require innovation and creation as well as full attention in helping students learn easily and happily. Efforts to make this happen, we are KKN students together with our supervisors, through this PKM activity at Madrash Tsanawiyah Nurul Jadid which has the aim of providing insight and experience in designing an Arabic language learning media with two forms of activity, the first is the provision of material and the second is the preparation of learning media environment-based in class VII odd semester 2020/2021 academic year.